2012
DOI: 10.7783/kjmcs.2012.20.2.108
|View full text |Cite
|
Sign up to set email alerts
|

The Preclinical and Clinical Effects of Herbal Product Containing Rosa mutiflora Roots Extracts as a Main Component on the Hair Growth Promotion

Abstract: : In this study, to develop hair growth agents using natural products which has excellent ability to promote hair growth effect and fewer side effect, animal experiment and clinical trials was performed to evaluate hair growth promotion effect of herbal product containing Rosa multiflora roots extracts as a main component (RMHP). 4-week-old male C57BL/6 mice were removed the dorsal hair using thioglycolate, and applied 15% EtOH solution as a negative control, 5% minoxidil as a positive control and RMHP to dors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…erefore, our study sought to investigate the hair-growth- Evidence-Based Complementary and Alternative Medicine promoting properties of NS extract through in vitro experiments using hDPCs and in vivo experiments using C57BL/6 mice. According to previous studies, antioxidant substances suppress hair loss-promoting cytokine activity, thereby promoting hair growth [34,36]. A study by Kim et al [37] reported that the average flavonoid content of 40 native plants was 70 mg NE/g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…erefore, our study sought to investigate the hair-growth- Evidence-Based Complementary and Alternative Medicine promoting properties of NS extract through in vitro experiments using hDPCs and in vivo experiments using C57BL/6 mice. According to previous studies, antioxidant substances suppress hair loss-promoting cytokine activity, thereby promoting hair growth [34,36]. A study by Kim et al [37] reported that the average flavonoid content of 40 native plants was 70 mg NE/g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to genetic factors, alopecia is caused by excessive stress, malnutrition, hormonal imbalances, and aging and is accompanied by a reduction in hair follicle size and anagen follicles [28][29][30]. Currently, many studies have been conducted using natural materials, such as herbal medicines and biopharmaceuticals, to identify therapeutic compounds capable of promoting hair growth and reducing hair loss [31][32][33][34]. While the activity of glutathione and SOD etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the current alopecia treatments, minoxidil and finasteride, have temporary effects and cause numerous side effects, there has been a growing interest in natural materials that encourage hair growth and have no side effects. Previous research indicates that high-antioxidant materials such as fermented Liriope platyphylla , green tea, onion extract, and wild rose root extract, have high anti-oxidant activities and high hair growth-promoting effects ( 22 – 25 ), with suppression of alopecia-promoting cytokine activities. Researchers are actively seeking natural materials that promote hair growth ( 26 ).…”
Section: Resultsmentioning
confidence: 99%